Bailando con lobos - Costner, Kevin, 1955- (Madrid IDA films, 1990)
Lt. John Dunbar, exiled to a remote western Civil War outpost, befriends wolves and Indians, making him an intolerable aberration in the military.
Para todos los públicos
Idiomas : castellano e inglés. Subt. : castellano
Kevin Costner, Mary McDonnell, Graham Greene
Keywords: Películas cinematográficas -- DVD